2019
DOI: 10.18097/pbmc20196505407
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a neuroprotective dose of isatin or deprenyl to mice on the profile of brain isatin-binding proteins

Abstract: Isatin (indol-2,3-dione), an endogenous biofactor found in the brain, peripheral tissues and biological body fluids of humans and animals, exhibits a wide range of biological and pharmacological activities. They are realized via interaction with numerous isatin-binding proteins. Some of these proteins identified during proteomic profiling of the brain are involved in the development of neurodegenerative pathology. In the context of the neuroprotective effect, the effect of isatin is comparable to the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 31 publications
0
5
0
2
Order By: Relevance
“…It should be noted that after administration of the neuroprotective doses of isatin (50-100 mg/kg), its concentration in the brain may exceed 70 µM [1,4]. Our recent study has shown that treatment of mice with a neuroprotective dose of isatin significantly influenced the proteomic profile of brain isatin-binding proteins [48]. The detected changes in the profile of isatin-binding proteins are consistent with the accumulation of administered isatin in the brain and its binding to target proteins, thus preventing subsequent protein binding to the affinity sorbent containing an isatin analogue as the affinity ligand [48].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…It should be noted that after administration of the neuroprotective doses of isatin (50-100 mg/kg), its concentration in the brain may exceed 70 µM [1,4]. Our recent study has shown that treatment of mice with a neuroprotective dose of isatin significantly influenced the proteomic profile of brain isatin-binding proteins [48]. The detected changes in the profile of isatin-binding proteins are consistent with the accumulation of administered isatin in the brain and its binding to target proteins, thus preventing subsequent protein binding to the affinity sorbent containing an isatin analogue as the affinity ligand [48].…”
Section: Introductionmentioning
confidence: 93%
“…Our recent study has shown that treatment of mice with a neuroprotective dose of isatin significantly influenced the proteomic profile of brain isatin-binding proteins [48]. The detected changes in the profile of isatin-binding proteins are consistent with the accumulation of administered isatin in the brain and its binding to target proteins, thus preventing subsequent protein binding to the affinity sorbent containing an isatin analogue as the affinity ligand [48]. Earlier, we also demonstrated that within a slightly different scheme of the animal experiment, pretreatment of rats with a neuroprotector dose of isatin prevented brain MAO B against irreversible inhibition by the mechanism-based inhibitor phenelzine [49].…”
Section: Introductionmentioning
confidence: 99%
“…Isatin interacts with numerous isatin-binding proteins, which have been identified during affinity-based proteomic profiling of mouse and rat brain tissue lysates (Buneeva et al, 2010(Buneeva et al, , 2012(Buneeva et al, , 2019Medvedev et al, 2020). proteins/enzymes; and (VI) Metabolism of amino acids and other nitrogenous compounds.…”
Section: Isatin-binding Proteinsmentioning
confidence: 99%
“…Además, en cultivos celulares la isatina presenta efectos protectores en neuronas dopaminérgicas y también se describe neuroprotección en el modelo de ratón de EP inducido por la neurotoxina 1-metil-4-fenil-1, 2, 3, 6tetrahidropiridina (MPTP) (8). Como agente neuroprotector, la isatina actúa sobre la gliceraldehído-3-fosfato deshidrogenasa (GAPDH), considerada posible diana terapéutica en patologías como la demencia senil, la epilepsia y la EP (9). El perfil proteómico de la isatina revela que este compuesto presenta capacidad para unirse a 200 proteínas cerebrales en ratones, mostrando un comportamiento análogo al de la selegilina (9).…”
unclassified
“…Como agente neuroprotector, la isatina actúa sobre la gliceraldehído-3-fosfato deshidrogenasa (GAPDH), considerada posible diana terapéutica en patologías como la demencia senil, la epilepsia y la EP (9). El perfil proteómico de la isatina revela que este compuesto presenta capacidad para unirse a 200 proteínas cerebrales en ratones, mostrando un comportamiento análogo al de la selegilina (9). Esto abre la puerta a plantear que, al igual que la selegilina, el posible efecto neuroprotector de la isatina podría ser independiente a la inhibición de la MAO-B.…”
unclassified